Apprentice Mobile Car Wash / Ahmad Azhari Amin Nordin ... [et al.] - Amin Nordin, Ahmad Azhari; Ahamad, Firdausiah; Hamidon, Huda; Abdullah, Nurul Hidayah; Ahmad Supian Chong, Siti Sharinah (Faculty of Information Management, 2006)
We would like to introduce our company as Apprentice Mobile Car Wash. Our nature of business is car wash business but not ordinary car wash we provide mobile car wash. We are tight down with preparation and production all the time. We would like to increase our staff strengths so that we can also carry out marketing at the same time. By doing this we do not mind increasing our targeted profit and since we are going to have professional teams, we are looking at higher returns then our targeted profit. We know that the possibilities of not reaching our target but since all the staff now are on their toes, with a good training and support from the General Manager, we are confident that we can make it. Additionally, we will provide excellent service, efficiently and expertly cleaning customer's cars so that they will be repeat users of the service. Our business is located in the heart of Shah Alam. This area has a number of benefits in terms of the market that it will provide for the business. That will also help to promote our company to the national market. The date of the commencement of our business is on the 1st of December 2006. We choose this type of business to position our company as the Best Mobile Car Wash Company in Malaysia through the organization. Our future prospect of this business is to be locally as well as internationally known throughout the world.